Transition from Cyclosporine-Induced Renal Dysfunction to Nephrotoxicity in an in Vivo Rat Model - Sereno, José (2014)
Cyclosporin A (CsA), a calcineurin inhibitor, remain the cornerstone of immunosuppressive regimens, regardless of nephrotoxicity, which depends on the duration of drug exposure. The mechanisms and biomarkers underlying the transition from CsA-induced renal dysfunction to nephrotoxicity deserve better elucidation, and would help clinical decisions. This study aimed to clarify these issues, using a rat model of short- and long-term CsA (5 mg/kg bw/day) treatments (3 and 9 weeks, respectively). Renal function was assessed on serum and urine; kidney tissue was used for histopathological characterization and gene and/or protein expression of markers of proliferation, fibrosis and inflammation. In the short-term, creatinine and blood urea nitrogen (BUN) levels increased and clearances decreased, accompanied by glomerular filtration rate (GFR) reduction, but without kidney lesions; at that stage, CsA exposure induced proliferating cell nuclear antigen (PCNA), transforming growth factor beta 1 (TGF-β1), factor nuclear kappa B (NF-κβ) and Tumor Protein P53 (TP53) kidney mRNA up-regulation. In the long-term treatment, renal dysfunction data was accompanied by glomerular and tubulointerstitial lesions, with remarkable kidney mRNA up-regulation of the mammalian target of rapamycin (mTOR) and the antigen identified by monoclonal antibody Ki-67 (Mki67), accompanied by mTOR protein overexpression. Transition from CsA-induced renal dysfunction to nephrotoxicity is accompanied by modification of molecular mechanisms and biomarkers, being mTOR one of the key players for kidney lesion evolution, thus suggesting, by mean of molecular evidences, that early CsA replacement by mTOR inhibitors is indeed the better therapeutic choice to prevent chronic allograft nephropathy.